How the (Un)Dead Became Modern: Supernatural Parodies of Modernity - García, Patricia (Margins/Marges/Margini, 2024)
This article focuses on nineteenth-century supernatural short fiction and its intersections with the urban in the European modern context. Through readings of texts by John Hollingshead, Charles Dickens and Flor O’Squarr, among others, this research addresses a form of the urban fantastic that employs satire and parody to reflect on the modern city project. In my analysis I compare different characters belonging to the ghost story tradition but whose traits relate to the discourses on progress and on being “a modern citizen”. As I aim to show, character construction, and how character relates to the urban context, underscores the question of what it is to be a modern ghost and, implicitly, what makes a successful (or failed) “modern” supernatural story.